Smart Indonesian language learning: A mobile-based inquiry model with local wisdom context to foster literacy and higher-order thinking skills - Yuliarti Yuliarti; Norhayati Norhayati (Privietlab, 2025)
This study aimed to develop and test the effectiveness of a mobile-based inquiry learning model with the integration of local wisdom to improve students' academic literacy and higher-order thinking skills (HOTS) in learning Indonesian in higher education. This study used a quasi-experimental design with a pretest-posttest control group. The research instrument was validated through expert and empirical testing, resulting in a validity coefficient of r count > r table (0.361), and Cronbach's alpha reliability between 0.86 and 0.89. The results showed an increase in academic Literacy with N-Gain of 0.63 in the experimental group compared to 0.29 in the control group, and an increase in HOTS with N-Gain of 0.60 in the experimental group compared to 0.27 in the control group. The t-test showed a significant difference (t-count 4.28 and 4.02 > t-table 2.00, p < 0.05). Student responses to this learning model were also very positive (88% positive responses). These findings indicate that integrating inquiry models, mobile learning, and local wisdom effectively creates a smart learning ecosystem relevant to the demands of the 21st century and can strengthen critical Literacy, HOTS, and students' cultural awareness.